IDENTIFICATION OF ADVERSE REACTIONS TO ORAL ANTICOAGULANT THERAPY IN HOSPITALIZED PATIENTS: A DESCRIPTIVE STUDY - dos, Santos Luciana; Martinbiancho, Jacqueline K.; Mezzalira, Paula B. (Asian Journal of Pharmaceutical Research and Development, 2014)
Vitamin K is a substance found at low concentrations in the human body, where it plays important roles in coagulation and calcium retention. The objective was to identify indications for use of vitamin K in a sample of hospitalized patients. In this descriptive, case-finding study, inpatients prescribed vitamin K during their hospital stays were assessed to identify the indications for vitamin K administration (thrombocytopenia due to oral anticoagulation or other drugs, vitamin K deficiency, or dietary deficiency). Patients from the Emergency Department and neonates were excluded. Overall, 161 cases were followed. In 73.3% of cases, the indication for vitamin K use was thrombocytopenia due to vitamin K deficiency. Seven patients (4.4%) had INRs outside the target range; of these, four (57%) developed bleeding, which was identified as an ADR. In the majority of patients given vitamin K, the indication was vitamin K deficiency.